Blood amyloid levels and risk of dementia in the Ginkgo Evaluation of Memory Study (GEMS): A longitudinal analysis. Issue 8 (27th June 2019) - Lopez, Oscar L.; Chang, Yuefang; Ives, Diane G.; Snitz, Beth E.; Fitzpatrick, Annette L.; Carlson, Michelle C.; Rapp, Stephen R.; Williamson, Jeffrey D.; Tracy, Russell P.; DeKosky, Steven T.; Kuller, Lewis H.
Abstract: Introduction: Both high or low plasma amyloid levels have been associated with risk of dementia in nondemented subjects. Methods: We examined baseline plasma β‐amyloid (Aβ) levels in relationship to incident dementia during a period of 8.5 years in 2840 subjects age >75 years; 2381 were cognitively normal (CN) and 450 mild cognitive impairment. Results: Increased plasma Aβ1‐40 and Aβ1‐42 levels were associated with gender (women), age, low education, creatinine levels, history of stroke, and hypertension. CN participants who developed dementia had lower levels of Aβ1‐42 and Aβ1‐42/Aβ1‐40 ratio compared with those who did not. Aβ levels did not predict dementia in mild cognitive impairment participants. Discussion: There was an inverse association between Aβ1‐42 and Aβ1‐42/Aβ1‐40 ratio to risk of dementia in CN participants. Cerebral and cardiovascular disease and renal function are important determinants of increased Aβ levels and must be considered in evaluations of relationship of plasma Aβ and subsequent risk of dementia.